Development of cross-protective Eimeria-vectored vaccines based on apical membrane antigens. Issue 7 (June 2018) - Pastor-Fernández, Iván; Kim, Sungwon; Billington, Karen; Bumstead, Janene; Marugán-Hernández, Virginia; Küster, Tatiana; Ferguson, David J.P.; Vervelde, Lonneke; Blake, Damer P.; Tomley, Fiona M.
Graphical abstract: Highlights: Eimeria tenella harbours four different stage-specific AMA1 paralogues. Et AMA1, but not Et AMA2, is involved in sporozoite invasion. Et AMA1, but not Et AMA2, induces significant protection against E. tenella challenge. Vaccination with transgenic E. tenella [ Em AMA1] parasites induces partial protection against challenge with Eimeria maxima . Abstract: Recently, the availability of protocols supporting genetic complementation of Eimeria has raised the prospect of generating transgenic parasite lines which can function as vaccine vectors, expressing and delivering heterologous proteins. Complementation with sequences encoding immunoprotective antigens from other Eimeria spp. offers an opportunity to reduce the complexity of species/strains in anticoccidial vaccines. Herein, we characterise and evaluate Et AMA1 and Et AMA2, two members of the apical membrane antigen (AMA) family of parasite surface proteins from Eimeria tenella . Both proteins are stage-regulated, and the sporozoite-specific Et AMA1 is effective at inducing partial protection against homologous challenge with E. tenella when used as a recombinant protein vaccine, whereas the merozoite-specific Et AMA2 is not. In order to test the ability of transgenic parasites to confer heterologous protection, E. tenella parasites were complemented with Em AMA1, the sporozoite-specific orthologue of Et AMA1 from E. maxima, coupled with different delivery signals to modify its trafficking and improve antigen exposure to the host immune system. Vaccination of chickens using these transgenic parasites conferred partial protection against E. maxima challenge, with levels of efficacy comparable to those obtained using recombinant protein or DNA vaccines. In the present work we provide evidence for the first known time of the ability of transgenic Eimeria to induce cross protection against different Eimeria spp. Genetically complemented Eimeria provide a powerful tool to streamline the complex multi-valent anticoccidial vaccine formulations that are currently available in the market by generating parasite lines expressing vaccine targets from multiple eimerian species.